АКТУАЛЬНІ ТЕНДЕНЦІЇ ДИЗАЙНУ ІНТЕР’ЄРІВ ЦЕНТРІВ СОЦІАЛЬНО-ПСИХОЛОГІЧНОЇ ДОПОМОГИ НАСЕЛЕННЮ - ШМЕЛЬОВА-НЕСТЕРЕНКО, О. Є.; КОЛОСНІЧЕНКО, О. В.; ОСТАПИК, С. В.; ЯЩЕНКО, М. А. (Art and Design, 2024)
Purpose: to identify key trends in the formation of the interior environment of social and psychological assistance centers based on an analysis of the needs of primary target groups of users. Methodology: the methodological foundation of the study includes a systematic approach, methods of comparative and visual analysis, and an examination of analogous projects of social and psychological assistance centers in Ukraine and abroad. Results: the analysis identified the main categories of individuals seeking help at social and psychological assistance centers (children, women, persons with disabilities, the elderly, and military personnel) and their key needs. Requirements for organizing the interior environment of such centers are defined, focusing on inclusivity, ergonomics, multifunctionality of spaces, and visual comfort. The study examined contemporary international approaches to designing such facilities, emphasizing the integration of natural materials, the creation of spaces that encourage social interaction, openness, and the use of advanced technologies. Trends aimed at improving the psychological comfort of visitors through user-friendly, modern, and intuitive environments were identified. Scientific novelty: lies in formulating requirements for the interior organization of social and psychological assistance centers based on user categories and identifying leading trends in the interior design of such facilities. Practical significance: the research findings can be utilized by designers and architects when planning social and psychological assistance centers.